Parameter Optimization of Coordinated Control System Based on Intelligent Algorithm. Issue 5 (March 2019) - Xu, Zhibin; Xiao, Li; Ouyang, Chunming; Zhang, Weidong
Abstract: This paper studies the issue of modeling and control of large unit coordinated control systems. The system is regarded as a three-input and three-output control object. Based on this, the system model is decoupled and the controller is designed. The controller is designed using an intelligent PID method, which based on genetic algorithm and fuzzy control model. The proposed method can optimize the control effect while ensuring the basic requirements, in order to achieve the goal of improving the dynamic process quality and improving the combustion efficiency.